Környezetvédelem versus környezetgazdálkodás - Papné Gáspár, Lujza; Sághi, Gábor (Tér és Társadalom, 1988)
The evidence of environmental crisis in the world is widely acknowledaed by international publications. But the reasons are not so unanimously judged: it is not made clear whether it is about the consequences of the social systems or the control systems, the mechanisms. We intend to prove that there is a permanent surplus demand for environment as a use value both in marketand in planned economies; demand surpasses environment supply. At the level of operation, both–market and planned–co-ordination formatismis are interested in the immediate profit of activities (though the concept of profit differs); wealth at the macro-economic level represents an abstract objective in the system: it is not supported by automatisms (mechanisms). The environmental factor remains an external objective for the economy, odd for the system, and this has an external appearance in the fact that it takes on a protective character instead of a managerial one. The final objective of our study is to lay the foundations of a reform process as a result of which the environmental factor would become an inteoral part of the economic system so that the present protection-oriented activity would change into environmental management. In our hypotheses it is also possible to elaborate a control system to serve the long-term realization of environmental management. The fundamental principle of our model of environmental manauement is based on the dominance of interests in environmental wealth instead of the interests in profits at present and on the parallel replacement of state interventions by automatisms or mechanisms. The emancipation of the living space function is an essential condition for the realization of interests in environmental wealth and that can be only done – in our view – in a regional perspektive.